Penerapan Metode ELECTRE Dalam Pemilihan Masker Wajah Terbaik Untuk Berbagai Jenis Kulit - Lola Alfiza; Muhammad Ridwan Lubis; Ilham Syahputra Saragih (LPPM STIKOM Tunas Bangsa, 2020)
The research aims to make the Decision Support System the best means of choosing masks with various types of facial skin especially Indonesian women, then recommending which masks are best to use. This problem can be ranked in the study. The method used in this research is the Electre method on the Decision Support System. Sources of research data obtained by interview and observation by giving a set of questions or statements to the customer used as respondents to be answered. The selection of face masks is used with several criteria including: (K1) oily skin, (K2) acne prone skin, (K3) dull skin, (K4) normal skin. And has sub criteria: color (c1), Texture (c2), Aroma (c3), Price (c4). The results of the research using the Electre method are expected to make it easier to determine the ranking of data winners from each alternative by the assessment process and facilitate system implementation.